Isolation of the protein and RNA content of active sites of transcription from mammalian cells - Melnik, Svitlana; Caudron-Herger, Maïwen; Brant, Lilija; Carr, Ian M.; Rippe, Karsten; Cook, Peter R.; Papantonis, Argyris (Nature protocols, 2016)
Transcription factories contain all three mammalian RNA polymerases, each actively transcribing a different subset of genes. This protocol describes how to isolate large factory fragments for the analysis of associated protein and RNA content.